The Fiscal Regime Comparison of IRAN`s New Petroleum Contract (IPC) with Buy-Back Model: The Case study of Phases 4 & 5 of the South Pars Gas Field - Hadi Dibavand; Ali Taherifard; Ali Faridzad; Atefeh Taklif; mohammad mahdi bahrololoum (Pizhūhishnāmah-i Iqtiṣād-i Inirzhī-i Īrān, 2018)
IRAN`s new petroleum contract is a new generation of service contract which aimed to fix bugs from Buy-Back model. In this model some incentives have inserted to increase contractors' motivations. In this study, we consider fiscal differences and revenue division of the two models in the case of phases 4 & 5 of the South Pars gas field. This study is conducted by fiscal simulation for two mentioned models and comparison the results. It is concluded that, government revenue in Buy-Back model throughout the period of production in phases 4 & 5 is bigger around 29% and 11% respectively in regard of the net present value and the discounted net present value. Also, if in Buy-Back model, production decline starts at the first year after fiscal settlement with contractor by the rate of more than 3% yearly, then it is better for the government to employ new contract model instead of Buy-Back model regarding revenue